Generalized Lichen Nitidus in Identical Twins. (22nd November 2012) - Leung, Alexander K. C.; Ng, Jeffrey
Abstract : Lichen nitidus is an uncommon idiopathic chronic dermatosis characterized by minute, flesh-colored or hypopigmented, shiny papules commonly occurring on the abdomen, chest, genitalia, and extremities. The disorder is most often localized but, rarely, can become extensive or generalized. The occurrence of lichen nitidus during infancy is extremely rare. A perusal of the English literature revealed but two cases. We report two identical twins with lesions of generalized lichen nitidus noted at two months of age. The familial occurrence of lichen nitidus suggests that a genetic factor may be operative.